Manajemen Pembelajaran Kitab Kuning di Pesantren Husnul Hidayah Karang Tanjung Alian Kebumen - Makmun, Syukron (Mataram University, 2024)
This research is to know kitab kuning learning management starting from planning, implementation, and evaluation at Husnul Hidayah Islamic Boarding School Karang tanjung Alian Kebumen. This research uses qualitative approach, while the research method is descriptive method. Technique of data collection is done by interview technique, observation, and documentation study. While in analyzing the data used is data categorization and data interpretation. The result of this research is found that (1) Planning Kitab Kuning at Husnul Hidayah Islamic Boarding School Karang tanjung Alian Kebumen is done with meeting all Masyayih, teachers and administrators to determine as subject matter of kitab kuning depend on every grade / class and who are teachers teaching kitab kuning based on grade or class.(2)The implementation of teaching learning proses is done by preparing class, consist of 5 classes ; Ibtida class, Jurumiyah class, Imrithi class, Alfiyah Class and Balaghah class.(3)The evaluation of learning Kitab kuning is conducted at mid-term semester and past term semester. The evaluation includes oral and written evaluations that cover the subject matter at mid-term semester and past term semester.